Depositional Environment of the Rajamandala Formation Based on Foraminiferal Analysis from the Kemang Area, Cianjur Regency, Bogor Basin, West Java, Indonesia - Dianda Rahma Aulia; Budhi Setiawan; Sundus Ghaida Noor Azizah (Lembaga Penelititan dan Pengabdian kepada Masyarakat - Institut Teknologi Adhi Tama Suraba, 2026)
The Rajamandala Calcareous Sandstone Member (Omc) and the Rajamandala Limestone Member (Oml) represent mixed siliciclastic–carbonate and carbonate deposits within the Bogor Basin. This study aims to determine the depositional environments and to evaluate the stratigraphic relationship between these two units by integrating geological mapping and micropaleontological analysis. Biostratigraphic analysis based on planktonic foraminifera indicates that both the Calcareous sandstone unit of the Rajamandala Calcareous Sandstone Member (Omc) and the Rajamandala Limestone Member (Oml) were deposited during the Early Miocene (Zones N7–N8). Benthic foraminiferal assemblages indicate deposition within an inner–middle neritic environment for both units. Field observations document a direct contact between the two lithologies, while geological mapping shows calcareous sandstone becoming increasingly abundant toward the southwest and limestone becoming progressively dominant toward the northeast. The equivalent ages, similar depositional environments, and observed field relationships are consistent with the interpretation that the two units were deposited contemporaneously and exhibit lateral facies variation within the same shallow marine depositional system.